Organic fertilizers in increase of hazelnut yield - Nikipelova, O.; Pyliak, N.; Hodorchuk, V. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2024)
Goal. To assess the effect of various organic fertilizers on the yield of hazelnut plantations in the conditions of the Southern Steppe of Ukraine.Methods. Field experiment, laboratory-analytical, comparative.Results. The influence of organic fertilizers of various origins was studied (cattle manure; chicken droppings; Biofertilizer No. 1 — sewage sludge (SW) of the biological treatment station (SBO) «Pivdenna» in Odesa + winter wheat straw + Microbacterium barkeri LP-1 (M. b.); Biofertilizer No. 2 — «Southern» SBO + sunflower seed husks + M. b.; «Pivdenna» SBO, Odesa) on the agrochemical parameters of ordinary medium-humus chernozem in the conditions of the Southern Steppe of Ukraine for the cultivation of hazelnuts. It is shown that in comparison with the control of 2021 and 2022, an increase in the content of easily hydrolyzed nitrogen, mobile forms of phosphorus and potassium, and organic matter is noted in all variants of the experiment.Conclusions. The use of organic fertilizers of various origins for the cultivation of hazelnuts in the conditions of the Southern Steppe of Ukraine helps to increase the content of the main agrochemical indicators of the soil — easily hydrolyzed nitrogen (91.0—98.0 mg/kg with 84.0 mg/kg — control), mobile phosphorus compounds (174.75—306.30 mg/kg at 138.75 mg/kg — control), potassium (112.00—166.90 mg/kg at 108.40 mg/kg — control) and organic matter (3.78—4.18% and 3.76% — control). The advantages of biofertilizers No. 1 and No. 2 based on sewage sludge with the use of vegetable fillers (winter wheat straw and sunflower seed husks) and the phosphate-mobilizing bacterium Microbacterium barkeri LP-1 are shown. Organic fertilizers contribute to the increase in the content of nutrients in the soil, the activation of the activity of eco-trophic groups of microorganisms, which leads to an increase in the biological activity of the soil and, accordingly, the yield of agricultural crops.